Enhancement of superoxide dismutase gene expression in mice following the administration of cinnamon bark extract - Ahda Yuni; Rahma Mustika; Nilasari Ratna; Lyrawati Diana (BIO Web of Conferences)
Proliferation of free radicals in the body, particularly in the form of reactive oxygen species (ROS), induces oxidative stress. One can enhance the antioxidant levels in the body by ingesting antioxidant substances. The cinnamon bark (Cinnamomum zeylanicum) is rich in flavonoids, cinnamic acid derivatives, coumarins, and polyfunctional organic acids. These compounds can serve as significant antioxidants in neutralizing radicals. The objective of this study was to investigate the impact of cinnamon extract on the expression of the superoxidase dismutase (SOD) gene in hepatocytes and spermatozoa of male mice. The treatments included: C: no administration of cinnamon extract, T1: administration of cinnamon extract at a concentration of 75 mg/kgBW, T2: administration of cinnamon extract at a concentration of 150 mg/kgBW. The amount of SOD cDNA after cinnamon extract administration was quantified using quantitative real-time PCR with β-Actin as internal control. This study shows that cinnamon extract (Cinnamomum zeylanicum) had a statistically significant effect (p < 0.05) on the upregulation of the superoxidase dismutase (SOD) gene expression in sperm (3.44) as well as liver cells (3,73) of male mice. The optimal dosage is 150 mg/kg body weight.